Alternative Representations of Business Process Models for Enhanced Understanding by People: A Systematic Mapping Study - Classe, Tadeu Moreira de; Castro, Ronney Moreira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Business process models are essential resources in business process management approaches that allow people to understand how an organization works. With business process models, organizations can reflect on process improvements and bring innovation to their services and products. In this context, it is fundamental for the people involved in the organization to understand how the process is performed to avoid misunderstandings and losses. Problem: Although there are several ways to represent a business process model, it is challenging to find alternative representations apart from traditional approaches (graphical and textual) and identify non-traditional approaches, goals, advantages, disadvantages, audiences, etc. Solution: Therefore, in this paper, we explored how alternative representations of business process models are used to enhance people’s understanding. Method: We planned, described, and performed a systematic mapping of the literature (SML) for that. Summary Results: In the search step, we found 322 primary studies, but after a careful evaluation criteria analysis by peer review, we accepted only 23. The results point to several alternative business process model representations, highlighting the potential for enhancing people’s understanding. Additionally, we presented the advantages and disadvantages of alternative model representations related to specified audiences. Contributions to IS: Thus, this study brings contributions to the IS field by identifying aspects of alternative representations of business process models, which bring new ideas and reflections to explore new technological approaches to make organizational contexts more understandable and accessible for people. In addition, this research is aligned with the GranDSI-BR 2016-2026, once they approach innovative themes related to IS in an open and connected world.